VALIDITAS MODUL PRAKTIK PERKANTORAN MENGGUNAKAN METODE PEMBELAJARAN ROLE-PLAYING BERBASIS KEBUTUHAN INDUSTRI - Febrika Yogie Hermanto; Siti Sri Wulandari; Jazi’ Muyassaroh; Berlina Hidayati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2022)
Office practice learning in Vocational High Schools (VHS) is not fully following the needs of the industry because the learning carried out is still partial to each Basic Competence (KD) in the curriculum. The purpose of this study is to reveal the validity of the product resulting from the development of the office practice module using the role-playing method based on industry needs. This researchis a type of development research using the ADDIE model. The research results are focused on the module assessment results by material experts, design experts, and learning experts. The results of this study indicate that the module is considered very feasible by the expert with an average score of 4.44 out of a maximum score of 5. The assessment of the material expert is 4.50, the assessment of the learning expert is 4.30, and the assessment of the design expert is 4.52. Thus, it can be stated that the resulting product is valid and feasible to use for the target group. Modules that are valid and feasible to use are expected to achieve the learning objectives that have been set.